Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1016/s0370-2693(98)01318-5
|View full text |Cite
|
Sign up to set email alerts
|

Lattice study of UA(1) anomaly: the role of QCD-monopoles

Abstract: We investigate the role of QCD-monopoles for the U A (1) anomaly in the maximally abelian gauge within the SU(2) lattice gauge theory. The existence of the strong correlation between instantons and QCD-monopoles in the abelian gauge was already shown by both analytic and numerical works including the Monte Carlo simulation. Their interrelation brings us a conjecture that the presence of QCD-monopoles plays a considerable role on the U A (1) anomaly.We find an evidence for our conjecture on a determination of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…Thus we have concluded that the topological nature is substantially inherited by QCD-monopoles. This conclusion is consistent with our previous study [33], which shows that QCD-monopoles strongly correlate with the presence of fermionic zero-modes in the MA gauge.…”
Section: Discussionsupporting
confidence: 94%
“…Thus we have concluded that the topological nature is substantially inherited by QCD-monopoles. This conclusion is consistent with our previous study [33], which shows that QCD-monopoles strongly correlate with the presence of fermionic zero-modes in the MA gauge.…”
Section: Discussionsupporting
confidence: 94%
“…To explain this phenomenon, 't Hooft [2] and Mandelstam [3] provided a convincing description that a magnetic monopole that condenses in the QCD vacuum causes the dual Meissner effect and that color charged particles are confined. A significant number of simulations have been conducted under lattice gauge theory, and sufficient results have been obtained that support this explanation [4][5][6][7][8][9][10][11]. Thus, this scenario seems to be widely accepted.…”
Section: Jhep09(2020)113mentioning
confidence: 92%
“…Recent studies show remarkable facts that instantons are directly related to monopoles [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] in the abelian gauge, although these topological objects belong to different homotopy group. For example, in the Polyakov-like gauge [29], monopoles appear due to the existence of the hedgehog configurations near instanton centers.…”
Section: Introductionmentioning
confidence: 99%